Controlling electron flow in anisotropic Dirac materials heterojunctions: a super-diverging lens. (4th October 2018) - Betancur-Ocampo, Y
Abstract: Ballistic heterojunctions of Dirac materials offer the opportunity of exploring optics-like phenomena in electronic systems. In this paper, a new perfect lens through special positive refraction is predicted with omnidirectional Klein tunneling of massless Dirac fermions. The novel optics component called a super-diverging lens (SDL) is the counterpart of a Veselago lens (VL). The use of SDL and VL creates a device that simulates the ocular vision. This atypical refraction is due to electrons obeying different Snell's laws of pseudo-spin and group velocity in heterojunctions with elliptical Dirac cones. These findings pave the way for an electron elliptical Dirac optics and open up new possibilities for the guiding of electrons.